Assessment of Anterior Abdominal Wall Layers Thickness under the influence of Age and Sex, Using Computed Tomography Imaging in Ibn-Sina Hospital, Khartoum, Sudan 2021 - Abbas, Ayman E; Alrawi, Mohammad Hatem; Saeed, Esra Ali Mahjoub (Archives of Clinical and Biomedical Research, 2022)
Background: The anterior abdominal wall is made up of skin, superficial fascia, deep fascia, muscles, extraperitoneal fascia, and parietal peritoneum. The radiological assessment of muscle and fat properties is fundamental in muscle diseases and obesity. A few studies in particular measured the thickness of anterior abdominal wall muscles and fatty layer. Purpose: To study the measurements of anterior abdominal wall layers thickness using CT KUB scan. Material and Methods: This is a retrospective descriptive radiology centerbased- study of patients come for CT-KUB in Ibn Sina Specialized Hospital during the period July 2021 to December 2021. It includes 232 male and female patients of different age groups. Thickness measurements were taken from a single slice of CT-KUB scan at the level of L3 –L4. The influence of age and gender was investigated, as well as muscular asymmetry. Results: The thickness of abdominal subcutaneous fatty layer in male is 17.5 mm and 24.8 in females. The mean thickness of subcutaneous fatty layer in mm is 13.28, 23.56, 25.95 and 22.57 in all four groups respectively. The mean thickness of abdominal wall muscles in all patients in RA = 8.08 with a p value = .003, TA = 4.88 with a p value = .011, IO = 6.7 with a p value = .000 and EO = 5.39 with a p value = .000. The RT side show more thickness that is more obvious in RA (10.1 mm for right and 6 mm for left) and IO (8.7 mm for right and 4.7 mm for left). Pearson correlation test was used to test the correlation between the thickness of subcutaneous fatty layer and the muscles. The results show r=-.157 for TM, -.233 for IO, and -.210 for EO. The results were insignificant for RT & LT RA and LT TA muscles. Conclusion: The infl